Fit to Perform: A Profile of Higher Education Music Students’ Physical Fitness - Araújo, Liliana S.; Wasley, David; Redding, Emma; Atkins, Louise; Perkins, Rosie; Ginsborg, Jane; Williamon, Aaron (Frontiers in Psychology, 2020)
Musicians are often called athletes of the upper body, but knowledge of their physical and fitness profiles is nonetheless limited, especially those of advanced music students who are training to enter music’s competitive professional landscape. To gain insight into how physical fitness is associated with music making, this study investigated music students’ fitness levels on several standardized indicators. 483 students took part in a fitness screening protocol that included measurements of lung function, flexibility (hypermobility, shoulder range of motion, sit and reach), strength and endurance (hand grip, plank, press-up), and sub-maximal cardiovascular fitness (3-min step test), as well as self-reported physical activity (IPAQ-SF). Participants scored within ranges appropriate for their age on lung function, shoulder range of motion, grip strength, and cardiovascular fitness. Their results for the plank, press up, and sit and reach were poor by comparison. Reported difficulty (22%) and pain (17%) in internal rotation of the right shoulder were also found. Differences between instrument groups and levels of study were observed on some measures. In particular, brass players showed greater lung function and grip strength compared with other groups, and postgraduate students on the whole were able to maintain the plank for longer but also demonstrated higher hypermobility and lower lung function (FEV1) and cardiovascular fitness than undergraduates. 79% of participants exceeded the minimum recommended weekly amount of physical activity, with singers the most physically active group and keyboard players, composers, and conductors the least active. IPAQ-SF scores correlated positively with lung function, sit and reach, press-up and cardiovascular fitness suggesting that, in the absence of time and resources to carry out comprehensive physical assessments with musicians, this one measure alone can provide useful insights. The findings indicate that music students have adequate levels of general health-related fitness, and we discuss whether adequate fitness is enough for people undertaking physically and mentally demanding activities such as making music. We argue that musicians could benefit from strengthening their supportive musculature and enhancing their awareness of strength imbalances.